2019
DOI: 10.3390/biom9070277
|View full text |Cite
|
Sign up to set email alerts
|

Association of Asymmetric Dimethylarginine and Diastolic Dysfunction in Patients with Hypertrophic Cardiomyopathy

Abstract: Despite genetic heterogeneity, early manifestation of diastolic dysfunction (DD) is common in hypertrophic cardiomyopathy (HCM). Nitric oxide (NO) may contribute to myocardial relaxation. NO synthases (NOS) use l-arginine (Arg) as a substrate, as asymmetric dimethylarginine (ADMA) is a direct endogenous inhibitor of NOS. This study aimed to analyze the association of Arg and its derivates, i.e., l-homoarginine (hArg), ADMA and symmetric dimethylarginine (SDMA), with DD in HCM patients. In 215 HCM patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Asymmetric dimethylarginine (ADMA) competes with L-arginine to the same binding site of nitric oxide synthase and this affects the oxidative stress process [ 34 ]. Cordts and colleagues (2019) suggested that high levels of ADMA in the circulation may reduce nitric oxide production and impaired myocardial relaxation in patients with hypertrophic cardiomyopathy (HCM) [ 35 ]. A high concentration of ADMA was also associated with increasing severity of diastolic dysfunction, the early manifestation of HCM.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…Asymmetric dimethylarginine (ADMA) competes with L-arginine to the same binding site of nitric oxide synthase and this affects the oxidative stress process [ 34 ]. Cordts and colleagues (2019) suggested that high levels of ADMA in the circulation may reduce nitric oxide production and impaired myocardial relaxation in patients with hypertrophic cardiomyopathy (HCM) [ 35 ]. A high concentration of ADMA was also associated with increasing severity of diastolic dysfunction, the early manifestation of HCM.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…Interestingly, only the LVEDV allowed for significant differentiation between healthy patients and those suffering from an underlying cardiac disease. This makes sense, as HCM or hypertensive heart disease typically initially present with diastolic dysfunction and only lead to reduced EF in later stages of the disease [ 44 , 45 ]. All strain parameters correlated significantly only to the LVEDV which underlines the fact that strain as well as the LVEDV were the more susceptible markers for earlier identification of cardiac pathologies within our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms found at the intersection of impaired myocardial relaxation and HCM are scarce, they indicate the leading role of NO homeostasis and a contribution of calcium homeostasis and collagen induction in their common pathogenesis. Cordts et al (2019) suggested that higher N, N-dimethylarginine (also known as asymmetric dimethylarginine, ADMA) plasma concentrations might lead to a decreased NO production and an impaired myocardial relaxation in HCM patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of HCM varies widely [ 1 , 3 , 7 , 8 ]: some patients are asymptomatic [ 1 , 7 , 13 ], while others manifest symptomatic left ventricular outflow tract obstruction (LVOTO) [ 7 , 8 ], atrial fibrillation (AF) [ 3 , 8 ], sudden cardiac death (SCD) [ 3 , 7 , 13 , 14 ], or heart failure (HF) [ 1 , 3 , 10 , 11 ]. Pathophysiologic features of HCM include cardiomyocyte hypertrophy [ 15 , 16 ], cardiomyocyte disarray [ 16 , 17 ], myocardial remodeling [ 18 , 19 ], fibrosis [ 3 , 20 , 21 ], myocardial hypercontractility [ 22 , 23 ], impaired myocardial relaxation [ 20 , 24 ], myocardial stiffness [ 17 , 20 ], diastolic dysfunction [ 13 , 14 , 17 ], coronary microvascular dysfunction [ 25 , 26 ], and myocardial ischemia [ 25 , 27 ], but the underlying molecular mechanisms are poorly understood. Molecular determinants of the disease presentations are also still not known.…”
Section: Introductionmentioning
confidence: 99%